Integration of Zakat and Taxes as Fiscal Policy Instruments - Abdussalam; Asep Hasan Sulaeman; Nurwahyu Fikri Ardhitiana (Sekolah Tinggi Agama Islam Minhajul Haq, 2026)
This research is motivated by various public opinions regarding zakat and taxes, indicating that the role of taxes is not yet fully optimal in supporting government revenues, especially during economic crises. The objective of this research is to examine how zakat and taxes can be integrated as fiscal policy instruments. This research employs a qualitative method with a library research approach and an exploratory study. Data collection is conducted through documentation, which includes books, journals, online articles, and other relevant sources. The results indicate that zakat and taxes can be integrated as fiscal policy instruments. Based on the trilogy of fiscal policy functions—namely allocation, distribution, and stabilization—zakat and taxes share fundamental similarities in addressing national economic problems, particularly during inflation and financial crises. Therefore, zakat should be considered by the government as a complementary fiscal policy instrument to support state revenues.